NeuO: a Fluorescent Chemical Probe for Live Neuron Labeling1. Issue 8 (7th January 2015) - Er, Jun Cheng; Leong, Cheryl; Teoh, Chai Lean; Yuan, Qiang; Merchant, Paolomi; Dunn, Matthew; Sulzer, David; Sames, Dalibor; Bhinge, Akshay; Kim, Dongyoon; Kim, Seong‐Min; Yoon, Myung‐Han; et al.
Abstract To address existing limitations in live neuron imaging, we have developed NeuO, a novel cell‐permeable fluorescent probe with an unprecedented ability to label and image live neurons selectively over other cells in the brain. NeuO enables robust live neuron imaging and isolation in vivo and in vitro across species; its versatility and ease of use sets the basis for its development in a myriad of neuronal targeting applications.